Two decades' experience with a prospective biobank for urologic oncology: research, clinical care, and the patients' view - Huber, Johannes; Herpel, Esther; Jakobi, Hildegard; Hadaschik, Boris; Pahernik, Sascha; Hohenfellner, Markus (Urologic oncology, 2013)
Objectives: Collection of clinical data and associated tissue samples has become an essential tool for oncologic research. Since 1990, efforts have been ongoing to implement prospective documentation of all oncologic cases in our department accompanied by a special aftercare program ensuring regular visits and reliable data acquisition. Materials and methods: Our prospective database comprises a total of 6,567 cases covering all types of urologic malignancies: prostate (40.7%), renal (30.5%), urothelial (21.8%), testicular (5.8%), penile (0.8%), and other (0.4%). A specialized full-time documentalist supported by 3 student assistants entered 38,135 aftercare visits characterized by approximately 100 partly disease-specific items. The Institute of Pathology's general collection contains more than 6 million paraffin-embedded samples, and since 2005 the interdisciplinary Tissue Bank at the National Center for Tumor Diseases in Heidelberg has collected about 21,000 cryo-samples. Furthermore, we asked the opinion of 158 patients who attended our clinic for cancer surgery using a self-designed questionnaire. Results: Of 158 patients asked to be included in the biobank, from 09/07 through 02/08, none refused. Their additional questionnaire had a return rate of 81% (n = 128). Moral obligation for supporting medical research was realized by 95%, and circumstantial pressure to participate was not a relevant factor for 87%. Whereas only 68% were hoping for personal benefit, altruism seemed to be a much stronger motive: 96% believe others could be healed because of further medical progress; 93% wanted to be actively informed about recommended aftercare visits. Consequently, response rates in the “Heidelberg Cancer Maintenance Program” are constantly above 93%. Regarding research, a total of 144 scientific inquiries have been answered using our database since 1995. Within the last 5 years, 37 manuscripts originated from biobank data: herein, molecular markers and risk factors have been correlated with clinical outcome. Additionally, TNM-validation studies were conducted. Conclusions: Prospective collection of clinical data and corresponding tissue has become an indispensable research tool in oncology. In general, patients do not object tissue banking and embrace special aftercare programs.
Online 1 March 2012
Gesehen am 08.11.2018